Temporal expression of hypoxia-regulated genes is associated with early changes in redox status in irradiated lung - Jackson, Isabel L. (2012)
The development of normal lung tissue toxicity after radiation exposure results from multiple changes in cell signaling and communication initiated at the time of the ionizing event. The onset of gross pulmonary injury is preceded by tissue hypoxia and chronic oxidative stress. We have previously shown development of debilitating lung injury can be mitigated or prevented by administration of AEOL10150, a potent catalytic antioxidant, 24 hours after radiation. This suggests that hypoxia-mediated signaling pathways may play a role in late radiation injury, but the exact mechanism remains unclear. The purpose of this study was to evaluate changes in the temporal expression of hypoxia-associated genes in irradiated mouse lung and determine whether AEOL10150 alters expression of these genes. A focused oligo array was used to establish a hypoxia-associated gene expression signature for lung tissue from sham-irradiated or irradiated mice treated with or without AEOL10150. Results were further verified by RT-PCR. 44 genes associated with metabolism, cell growth, apoptosis, inflammation, oxidative stress and extracellular matrix synthesis were upregulated after radiation. Elevated expression of 31 of these genes was attenuated in animals treated with AEOL10150, suggesting that expression of a number of hypoxia-associated genes are regulated by early development of oxidative stress after radiation. Genes identified herein could provide insight into the role of hypoxic signaling in radiation lung injury, suggesting novel therapeutic targets, as well as clues to the mechanism by which AEOL10150 confers pulmonary radioprotection.